Carbon spheres@MnO2 core-shell nanocomposites with enhanced dielectric properties for electromagnetic shielding. Issue 1 (December 2017) - Wang, Huiya; Zhang, Zhifan; Dong, Chengjun; Chen, Gang; Wang, Yude; Guan, Hongtao
Abstract Carbon spheres (CS)@MnO2 core-shell nanocomposites, with MnO2 nanoflakes uniformly coating at the surface of CS cores, were successfully synthesized by a facile water-bathing method. MnO2 amounts is estimated to be 24.7 wt% in CS@MnO2 nanocomposites. A high dielectric loss value and an electromagnetic shielding effectiveness of 16‒23 dB were observed for the CS@MnO2 in the frequency range of 8‒18 GHz, which is mainly attributed to the enhanced absorption loss. The incorporation of the CS with MnO2 improves the electrical conductivity. Meanwhile, the electromagnetic impendence matching has been significantly ameliorated. Moreover, the increasing interfaces between the CS and MnO2 facilitate the microwave attenuation as well. Thus, the electromagnetic shielding performances were greatly enhanced. Our findings provide an effective methodology for the synthesis of the CS@MnO2 core-shell nanocomposite for potential electromagnetic applications.